2021
DOI: 10.1002/adfm.202009449
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Electrocatalytic Methanation of CO2 at Ambient Conditions

Abstract: Electrochemical CO2 reduction under ambient conditions is a promising pathway for conversion of CO2 into value‐added products. In recent years, great achievements have been obtained in the understanding the mechanism and development of efficient and selective catalysts for electrochemical CO2 reduction. However, the electrochemical CO2 reduction is still far from practical applications. Based on the gap between current research and practical applications, the state‐of‐the‐art of the theoretical and experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 220 publications
(499 reference statements)
0
81
0
Order By: Relevance
“…The decrease in FE HCOOH could be attributed to the specific design of the flow reactor in which the KHCO 3 electrolyte is supplied as the main reactant with a low concentration of the dissolved CO 2 , HCO 3 – , and CO 3 2– species, in addition, the local concentrations of H + donors are still available and competitive around the electrocatalyst surface resulting in a reduction of the Faradic efficiency of formic acid. [ 35 , 36 ] This finding brings new prospects for realizing high CO 2 ‐to‐HCOO – ‐current densities on effective Zn(Pb) bimetallic electrocatalyst.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in FE HCOOH could be attributed to the specific design of the flow reactor in which the KHCO 3 electrolyte is supplied as the main reactant with a low concentration of the dissolved CO 2 , HCO 3 – , and CO 3 2– species, in addition, the local concentrations of H + donors are still available and competitive around the electrocatalyst surface resulting in a reduction of the Faradic efficiency of formic acid. [ 35 , 36 ] This finding brings new prospects for realizing high CO 2 ‐to‐HCOO – ‐current densities on effective Zn(Pb) bimetallic electrocatalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Among these technologies, electrocatalytic CO 2 reduction reaction (CRR) has attracted greater attention by virtue of its mild operating conditions and great potential to scale up. [340][341][342][343] Although significant progress is experienced in this field, there are still major challenges, which hinder the understanding of CRR. 344 Pioneering studies on CRR involving different metals was initiated by Hori and co-workers more than thirty years ago.…”
Section: Valuable Fuels and Chemicals Via Co 2 Reduction Reactionmentioning
confidence: 99%
“…Electrocatalytic CO 2 reduction reaction (CO 2 RR) is an effective way to produce formic acid/formate, which is appealing for tackling the complications related to the rising CO 2 levels and facilitating a sustainable closed carbon cycle at the same time. [ 3–7 ] Hori et al. reported that metal electrodes such as Bi, Sn, Pb, Hg, and In, can prompt efficiently electroreduction of CO 2 to formate.…”
Section: Introductionmentioning
confidence: 99%